2019
DOI: 10.1002/rcs.2026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uterine weight on robotic hysterectomy: Analysis of 500 cases in a single institute

Abstract: Backgrounds Robotic surgeries have been used frequently for benign diseases in gynecology. However, the advantage of robotic surgery for huge uterus is unclear. Methods We analyzed surgical outcomes of 527 patients who underwent robotic hysterectomies for benign diseases, separating uterine sizes into five groups by every 250 g. Results Median operative time in the five groups was 123 minutes (<250 g), 130 minutes (250‐500 g), 144 minutes (500‐750 g), 180 minutes (750‐1000 g), and 170 minutes (>1000 g). Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
1
10
2
Order By: Relevance
“…Patients were divided into five groups based on uterine size: <250 g, 250-500 g, 500-750 g, 750-1000 g, and >1000 g. Estimated blood loss and operating time showed a linear relationship with uterine size (p-value<0.001). The blood loss during surgery was more in a group with uterus weight >1000 g [ 15 ]. Similar to the study by Akazawa et al, we also found that mean blood loss and operating time increased as the size of the uterus increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients were divided into five groups based on uterine size: <250 g, 250-500 g, 500-750 g, 750-1000 g, and >1000 g. Estimated blood loss and operating time showed a linear relationship with uterine size (p-value<0.001). The blood loss during surgery was more in a group with uterus weight >1000 g [ 15 ]. Similar to the study by Akazawa et al, we also found that mean blood loss and operating time increased as the size of the uterus increased.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, totally nine patients had intra-operative and post-operative complications and this was similar in both groups (p < 0.48). Akazawa et al in 2019 studied the outcome of robotic hysterectomy in 527 patients who had 18 cases (3.4%) with postoperative complications [ 15 ]. Petersen et al in 2018 studied urologic injury with a robotic hysterectomy and observed urologic injury in 0.92% of cases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uterine weight, in particular, varies from a small uterus to a large uterus weighing more than 1 kg [3,4], depending on the indications. Most previous studies have reported that surgical difficulty increases with increasing uterine weight, suggesting that uterine weight affects surgical outcomes, such as operative time, blood loss, and conversion to laparotomy [5][6][7][8]. However, the impact of uterine weight on the surgical outcomes of robot-assisted hysterectomy has not been elucidated, with previous studies showing disparate results.…”
Section: Introductionmentioning
confidence: 99%